ACC Limited : Project 30-30 - Mukherjee, Saral, (SAGE Knowledge. Cases., 2011)
ACC limited had set itself a challenging target of producing and selling 30 million tonnes of concrete in 2011. The problem however, was that those 30 million tonnes of concrete needed to be transported putting a huge strain on logistics. The focus of the case is on analysing the supply chain in an integrated manner, considering the options of ACC to increase their market presence.